A realistic flow phantom model of the carotid artery in preterm infants for training and research. (August 2020) - Pereira, Sujith; Reeves, Jonathan; Birch, Malcolm; Finton-James, Sakthi; Verma, Komal; Krug, Robert; Sinha, Ajay; Kempley, Stephen
Introduction: Cerebral blood flow is increasingly monitored in preterm infants. Doppler ultrasound of the carotid artery is a widely available method but is operator dependent. Our aim was to design and produce a realistic flow phantom model of the carotid artery of preterm infants. Methods: Data from cerebral blood flow measurements using Doppler ultrasound of the right common carotid artery from 21 premature newborn infants were used to produce a Doppler flow phantom model with three different vessel diameters. Vessel diameter, continuous and pulsatile flow volume measurements were performed by two blinded observers (with more than eight and 20 years of experience). Results: Vessel diameter measurements using the phantom were underestimated by 7%. Continuous flow volume measurements were overestimated by 7% by both observers (observer 1 mean difference 1.5 ± 1.96 SD −3.3 to 6.3 ml/min versus observer 2, 1.9 ± 1.96 SD −3.6 to 7.4 ml/min). Pulsatile flow measurements were overestimated by 12.6% by observer 1 (2.7 ± 1.96 SD −0.6 to 5.9 ml/min) and by 7.8% by observer 2 (1.7 ± 1.96 SD −1.6 to 4.9 ml/min). There was good interobserver and intraobserver reliability for the majority of measurements using continuous and pulsatile flow. Conclusion: It is feasible to produce a realistic flow phantom model of the neonatal carotid artery of preterm infants. Diameter measurements were underestimated and flow measurements were overestimated. These errors fell within acceptable limits for in vivo measurements. If these limitations were related to materials, this could be explored using a wall-less model. The flow phantom could be utilised for research and training clinicians in measuring cerebral blood flow using the carotid artery in this vulnerable group of infants.